Revolutionizing Cosmetic Ingredients: Harnessing the Power of Antioxidants, Probiotics, Plant Extracts, and Peptides in Personal and Skin Care Products - Hye Yung Choi; Yun Jung Lee; Chul Min Kim; Young-Mi Lee (Cosmetics)
The burgeoning interest in natural components in personal care products has led to significant research and development of ingredients such as plant extracts, antioxidants, peptides, and probiotics. These components have been recognized for their potential to enhance skin health through various mechanisms, addressing consumer demand for products that are both effective and benign. Plant extracts, known for their rich composition of bioactive compounds, offer a myriad of benefits including antioxidant, anti-inflammatory, and antimicrobial properties, making them invaluable in skin care formulations. Antioxidants, derived from both plants and other natural sources, play a pivotal role in protecting the skin from oxidative damage, thereby preventing premature aging and promoting skin vitality. Bioactive peptides have garnered attention owing to their multifunctional activities that include promoting collagen synthesis, inhibiting enzymes responsible for skin degradation, and reducing inflammation, thereby contributing to skin regeneration and anti-aging. Probiotics have expanded their utility beyond gut health to skin care, where they help in maintaining skin microbiome balance, thus enhancing skin barrier function and potentially mitigating various skin disorders. The purpose of this review is to explore the individual roles of plant extracts, antioxidants, peptides, and probiotics in personal care products, while emphasizing their synergistic effects when combined. By integrating these natural components, this paper aims to highlight the potential for developing innovative skincare formulations that not only address specific skin concerns but also contribute to overall skin health, aligning with the increasing consumer preference for natural and holistic skincare solutions.